2018
DOI: 10.1186/s13063-018-2513-y
|View full text |Cite
|
Sign up to set email alerts
|

ADJunctive Ulinastatin in Sepsis Treatment in China (ADJUST study): study protocol for a randomized controlled trial

Abstract: BackgroundSepsis is a major challenge in critical care and is associated with high mortality. Current management of sepsis and septic shock remains mainly supportive. Both basic and clinical research has shown that ulinastatin can improve the prognosis of sepsis. The aim of this trial is to evaluate the efficacy and safety profiles of ulinastatin compared with placebo.Methods/designIn this multi-center, double-blind, randomized placebo-controlled trial we are recruiting a total of 348 subjects meeting “The Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…Thus, multicenter, large sample, randomized clinical trials are still urgently needed to further evaluate the effects of UTI in patients with sepsis. At present, ADJunctive Ulinastatin in Sepsis Treatment in China (ADJUST study), a large sample, multi-center, double-blind, randomized, parallel-group, placebo-controlled trial is being conducted in mainland China (Jiang et al, 2018). The aim of this trial is to further evaluate the efficacy and safety profiles of UTI.…”
Section: Limitationsmentioning
confidence: 99%
“…Thus, multicenter, large sample, randomized clinical trials are still urgently needed to further evaluate the effects of UTI in patients with sepsis. At present, ADJunctive Ulinastatin in Sepsis Treatment in China (ADJUST study), a large sample, multi-center, double-blind, randomized, parallel-group, placebo-controlled trial is being conducted in mainland China (Jiang et al, 2018). The aim of this trial is to further evaluate the efficacy and safety profiles of UTI.…”
Section: Limitationsmentioning
confidence: 99%
“…This study shows that fluid resuscitation combined with ulinastatin have something to do with reducing mortality in sepsis patients after 30 d treatment. It has been reported that among 122 sepsis patients, there were one or more organ failure [13] treated with ulinastatin. It was found that in 28 d all-cause mortality in ulinastatin group was 7.3 % (4 deaths), while that in control group was 20.3 % (12 deaths) (p=0.045), which was the same as the results of our research.…”
Section: Resultsmentioning
confidence: 99%
“…Third, the evolving definition of sepsis may also explain the conflicting results. While early trials defined sepsis as the infection plus systematic inflammatory response syndrome (SIRS) 23 , more recent trails and the present study enrolled patients with sepsis-3.0 criteria 26 . There is large body of evidence that sepsis identified by these two definitions can be quite different 1 , 27 .…”
Section: Discussionmentioning
confidence: 99%